What makes primary care effective for people in poverty living with multiple chronic conditions?: study protocol - Barbeau David; Bedos Christophe P; Fortin Martin; Haggerty Jeannie L; Loignon Christine; Allen Dawn (BMC, 2010)
Abstract Background The inverse care law persists: people living in poverty have the greatest needs and face considerable challenges in getting the care they need. Evidence reveals that GPs encounter difficulties in delivering care to poor patients, while many of those patients feel stigmatized by healthcare professionals. Patients living in poverty report negative healthcare experiences and unmet healthcare needs. Indeed, there is a growing recognition in primary care research of the importance of addressing the capabilities and social conditions of the poor when delivering care. Few studies have looked at the factors contributing to effective and "socially responsive" care for people living in poverty. Methods/Design Our study adopts a qualitative ethnographic approach in four healthcare organizations in deprived areas of metropolitan Montreal (Québec, Canada), using patient shadowing techniques and interviews. Data will be collected through fieldwork observations and informal interviews with patients before and after consultations. We will observe medical consultations, care organization activities, and waiting areas and reception of patients. We will conduct a total of 36 individual interviews with 12 GPs and 24 patients. The interviews will be audio-recorded and transcribed for purposes of analysis. The analysis consists of debriefing sessions, coding and interpretive analysis. Discussion This study aims to investigate how positive healthcare interactions between physicians and patients can improve the management of chronic conditions. We hypothesize that factors related to care organization, to healthcare professionals' experience and to patients may enhance the quality of healthcare interactions, which may have positive impacts for preventing and managing chronic conditions. Our study will provide a unique set of data grounded in the perspectives of healthcare professionals and of patients living in poverty.